Export Potential as the Competitiveness Indicator of the Agri-Food Complex - Anatolyevna Yakovenko, Natalia; Anatolyevna Rodionova, Irina; Serafimovna Ivanenko, Irina; Arkadevna Kireeva, Natalia; Mikhailovna Sukhorukova, Antonina (International Journal of Engineering and Technology, 2018)
The paper deals with some theoretical approaches to determining the essence of the export potential, the features of its formation and development in the agri-food complex, the impact on the growth of competitiveness. This made it possible to clarify the definition of the export potential of the agri-food complex as an aggregate of competitive advantages. The specifics of the development of the export potential in the context of globalization and the development of international integration are revealed. The dynamics and structure of exports of food products and agricultural raw materials are analyzed; the physical capacity of the domestic markets of basic food products, the dynamics, and trends of its change are estimated. Excessive growth in the volume of production of agricultural products can lead to oversaturation of the domestic market, a decrease in the profitability of domestic producers, worsening the financial situation in the industry. Russia has a significant potential for integration into the world agri-food system. However, the main share of the export of the agri-food complex is made up of agricultural raw materials, primarily grains and oilseeds, which has an adverse effect on the structure of the complex and the rate of its development. The diversification of exports, the growth of exports of products with high added value will contribute to the sustainable development of agriculture and food industries. The development of the export potential of the Russian agri-food complex should be based not only on the active use of national competitive advantages but also on the formation of competitive advantages based on the international division of labor as well. The export-oriented strategy for the development of Russia's agri-food complex needs to be justified in the context of food security policy, which implies resolving the contradiction between national interests related to the saturation of domestic markets, and attitudes toward growing competitiveness in the world food markets, as well as the development and realization of the export potential.Â Â